(untitled) (Res Medica, 2014)
John F. Munro, M.B., Ch.B., M.R.C.P.(E), William A. Branford, B.Sc., Christopher Smith, M.B., Ch.B., M.R.C.P.(E), Geoffrey D. Hargreaves, James Williamson, M.B., Ch.B.. F.R.C.P.(E), John Parker, B.Sc. and Peter Calverly.